The new inquisitions : heretic-hunting and the intellectual origins of modern totalitarianism - Versluis, Arthur, 1959- (Oxford University Press, 2006)
'The New Inquisitions' begins with early Christianity, and traces heretic-hunting as a phenomenon through the middle ages and right into the 20th century, showing how the same inquisitional modes of thought recur both on the political Left and on the political Right.